Misperception of tiredness in young adults with insomnia. (22nd February 2016) - Akram, Umair; Ellis, Jason G.; Myachykov, Andriy; Barclay, Nicola L.
Summary: People with insomnia often exhibit interpretive biases to cues associated with their condition. This study examined whether individuals with insomnia display an interpretive bias, such that they misperceive facial attributes of tiredness in a disorder‐consistent manner. The efficacy of providing feedback related to the accuracy of participants' perception on later judgements of tiredness was further examined. Forty participants, 20 with DSM‐5‐defined insomnia disorder and 20 normal‐sleepers, participated. The perception of one's own facial appearance of tiredness was assessed twice over two consecutive days using a visual task whereby participants indicated when a morphing image of their face represented their current level of tiredness. Visual and verbal feedback, related to participants' degree of misperception, was provided on completion of Day 1 testing. Overall, individuals with insomnia perceived their own face as significantly more tired than a baseline neutral photograph was, whereas normal‐sleepers perceived themselves as appearing more alert. This pattern of results was only apparent on Day 1. Although no group × day interaction was established, mean scores suggest an improvement in perception on Day 2 amongst individuals with insomnia only. These findings suggest that individuals with insomnia exhibit a misperception of their facial attributes of tiredness, interpreting them in a disorder‐consistent manner. This finding adds to the body of literature on cognitive models of insomnia, demonstrating more general cognitive biases in the disorder. Further, the results provide suggestive evidence that this misperception may be reformed.